Parrhesía and necropolitics: new approaches around the victims - Molnár-Gábor, Ferenc Alajos (Revista Ethika+, 2020)
In this text we will examine the problematic relation between the notions of parrhesia, necropolitics and victim. Our work will be based in an examination of necropolitics and his intimate relation with Foucault’s biopower, with its resistances and effects. A particular resistance is contained in the notion of parrhesia, that with will be given its own modal modification in front of the effects of necropolitics under the examined circumstances. With the above, our intention is to make a portrait of a theory of "victims and parrhesia" under the context of necropolitics and non philosophy. We will make "use" in the most ethically way possible of visual material, demarking its respective theoretical limits. In last instance we like to propose (non)-parrhesia as a form of ethical and theoretical pragmatics according to the victims.